Faktor-Faktor Yang Berhubungan Dengan Kejadian Hipertensi Di Puskesmas Pasar Ikan Kota Bengkulu - Nurfadilah, Siski; Maryasari, Fikitri; Wulandari, Wulandari (Universitas Dehasen Bengkulu, 2025)
Hypertension is defined as systolic and diastolic blood pressure measurements that continuously exceed normal values. The prevalence of hypertension in Indonesia based on measurements of the population aged 18 years is 34.1%. Hypertension occurs in the 31-44 year age group at 31.6%, around 45.3% at the age of 45-54 years, and at the age of 55-64 years 55.2%. The aim of the research is to determine the risk factors for the incidence of hypertension at the Pasar Ikan Health Center in Bengkulu City in 2024. This research method is quantitative with a cross sectional design. The sample in this study amounted to 71 people, taken by accidental sampling. Data were processed using univariate and bivariate analysis with the chi-square test. The results of the research results of statistical tests showed that there was a significant relationship between the incidence of hypertension and age (p=0.001), showed that there was a relationship between obesity and the incidence of hypertension (p=0.001), showed that there was no significant relationship between stress and the incidence of hypertension (p=0.344 ). The suggestion is that the community health center can optimize preventive and promotive programs regarding factors related to the incidence of hypertension and it is hoped that hypertension sufferers will reduce their consumption of factors related to the incidence of hypertension and carry out regular check-ups at the Pasar Ikan Community Health Center.